Little book of Gucci : the story of the iconic fashion house - Homer, Karen (London : Welbeck, 2020)
One of the oldest Italian fashion brands in existence today, Gucci was founded in Florence in 1921. Guccio Gucci established his company with the goal of creating opulent luggage for Italy's wealthy and fashionable upper-classes. With the signature Gucci print of dark brown diamonds on a tan background, interlocking G logo and red and green stripe, the brand has gone on to become the last word in Italian luxury. Gucci's signature items - the belt, the bag, the loafer - transcend fleeting fashion trends, and have remained central to the house's identity into the twenty-first century. Under the stewardship of Tom Ford, Gucci epitomized the louche and mischievous 1990s aesthetic. Today, under Alessandro Michele, the brand's combination of romance and toughness is in hot demand. The Little Book of Gucci tells the story of this historic yet flourishing house, and the visionary looks that have cemented its place in fashion history.
Includes index.
Keywords: Fashion; Fashion design